HiSOR multimode undulator as a circularly polarized light source - Rybalchenko, G.V.; Smolyakov, N.V.; Shirasawa, K.; Morita, M.; Hiraya, A. (Вопросы атомной науки и техники, 2001)
A linear/helical multimode undulator, which is installed at storage ring in Hiroshima Synchrotron Radiation Center, is initially designed for the utilizing of circularly polarized light from its fundamental harmonic in the spectral range of 4 - 40 eV. Operating of the undulator in elliptical configuration may considerably extend this spectral region. This paper presents a study for the optimisation of operating parameters of a linear/helical multimode undulator with the aim to maximize the circularly polarized high-energy photons output. The comparison with the correspondent characteristics of synchrotron radiation from bending magnet is performed. The results presented here were obtained for the general case that provides a means of applying derived expressions for any kind of elliptical wiggler as well as bending magnet.